STRUKTUR KALIMAT MAJEMUK BAHASA MANDARIN (Analisis X-Bar) - Devi Alvionita Alindra (BAHAS, 2020)
AbstractThis study aims to explain the functional categories that apply to Chinese compound sentences and to explain the structure of Chinese compound sentences. The method used in this research is qualitative method. The findings in this study are that the complementary and conjunction functional categories have characteristics that must be present in every compound sentence in Chinese. Chinese compound sentences are grouped into two types, namely coordinative and subordinative compound sentences. Chinese coordinative compound sentence structure is: Spes + I + Pm + Komp + Pm + Komp; Komp + Spes + I + Pm + Komp; Spes + I + Komp + Spes + I + Pm + Komp; Spes + I + Komp + Pm + Komp; while the Chinese subordinative compound sentence structure is: Spes + I + Komp + Pm + Spes + I + Komp; Spes + I + Pm + Komp + Pm + Komp; Pm + Komp + Spes + I + Pm + Komp; Pm + Komp + Spes + I + Komp; Spes + I + Pm + Komp + Spes + I + Komp; Pm + Spes + I + Komp + Pm + Komp.Keywords: functional categories, Chinese compound sentence structure, x-bar theory. Abstrak Kajian ini bertujuan untuk menjelaskan kategori fungsional yang berlaku pada kalimat majemuk bahasa Mandarin dan untuk menjelaskan struktur kalimat majemuk bahasa Mandarin. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Temuan dalam penelitian ini yakni kategori fungsional komplemen dan konjungsi/pemerlengkap memiliki sifat yang wajib hadir pada setiap kalimat majemuk bahasa Mandarin. Kalimat majemuk bahasa Mandarin dikelompokkan menjadi dua jenis, yaitu kalimat majemuk koordinatif dan subordinatif. Struktur kalimat majemuk koordinatif bahasa Mandarin yaitu: Spes+I+Pm+Komp+Pm+Komp;Komp+Spes+I+Pm+Komp;Spes+I+Komp+Spes+I+Pm+Komp;Spes+I+Komp+Pm+Komp; sedangkan struktur kalimat majemuk subordinatif bahasa Mandarin yaitu:Spes+I+Komp+Pm+Spes+I+Komp;pes+I+Pm+Komp+Pm+Komp;Pm+Komp+Spes+I+Pm+Komp;Pm+Komp+Spes+I+Komp;Spes+I+Pm+Komp+Spes+I+Komp;Pm+Spes+I+Komp+Pm+Komp. Kata Kunci: kategori fungsional, struktur kalimat majemuk bahasa Mandarin, teori x-bar.